Peningkatan Pemahaman Siswa SMA N 1 Batang Gasan, kec.Batang Gasan, kab. Padang Pariaman, prov.Sumatera Barat. Tentang Pentingnya Etika Pancasila Guna Menangulangi Maraknya Balap Liar di Kalangan Remaja - Kintan Kurniadi Akroma; Desyra Putri Zaepa; Agus Wandi; Azizi Pratama; Shyfa Mulya Dita; Cut Aulia Astini; Devi Mariska; Farhan Rahmatul Akbar (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Illegal street racing is an activity that endangers both the riders and the surrounding community, as well as violating traffic laws. The implementation team from the Faculty of Economics and Business at Universitas Dharma Andalas conducted an outreach program in SMAN 1 Batang Gasan about the dangers of illegal street racing. This initiative aimed to raise awareness about legal compliance and road safety, thereby reducing the incidence of accidents caused by such activities by using an approach to Pancasila ethics. The methods employed included discussions, and Q&A sessions, supported by presentation media. The results indicated an increased understanding among participants regarding the risks and legal consequences of illegal street racing, along with a commitment to avoid such activities. It is anticipated that this outreach will contribute to creating a safer and more orderly environment